One-skein wonders for babies - 20160731 frey50; Durant, Judith, 1955-; Hoffman, Geneve (North Adams, MA Storey Publishing, 2015)
"Knit your beautiful single skeins into darling wearables, toys, blankets, and accessories for baby. Comforting and cozy for infants or stylish and sturdy for active toddlers, there's a perfect pattern for every child, every occasion,"--page [4] of cover.
Little Ensembles -- Little Tops -- Little Bottoms -- Little Dresses -- Little Hats -- Little Socks & Bootees -- Little Accessories -- Little Blankets -- Little Toys -- Little Miscellany.
Includes index.
Keywords: Knitting; Infants' clothing; Patterns